P578Multipoint pacing in cardiac resynchronization therapy - how to improve remodeling criteria and its impact in quality of life. (18th June 2020) - Nunes Ferreira, A; Antonio, P S; Aguiar-Ricardo, I; Rodrigues, T; Cunha, N; Santos, R P; Rigueira, J; Bernardes, A; Santos, I; Goncalves, S; Pinto, F J; De Sousa, J; et al.
Abstract: Background: Despite the reduction in mortality and hospitalization rates, resynchronization therapy still has 30-40% of non-responders. Several studies are ongoing to evaluate if novel programming techniques such as multipoint pacing (MPP) increase the conversion rate of non-responder to responder to CRT. However, there is still lack of information about conversion to super-responders and the impact in quality of life of MPP. Purpose: To evaluate the impact of MPP in conversion to super-responders and its impact in the quality of life of patients. Methods: Randomized clinical trial of non-AF patients with indication for CRT and who implanted the Quartet™ quadripolar left ventricle (LV) lead. After implant, CRTs were programmed on biventricular pacing according to the latest activated area for 6 months. After a 6-month follow-up, patients were randomized in a 1:1 fashion to MPP ON or MPP OFF. MPP was programmed with the two widest spaced LV electrodes and with a LV1-LV2 to LV2-RV delay of 5ms. Patients were followed-up for 12 months with a 6-month evaluation of NTproBNP, echocardiographic remodeling criteria (LV end systolic volume (ESV) and LV ejection fraction), and quality of life (QoL) evaluated by EQ-5D, Minnesota Living with Heart Failure (MLWHF) questionnaire and 6-minute walk test (6MWT). Results:  76 patients were included in this trial, 62 with a completed 12-month follow-up (average age 67.2 ± 10.2 years old, 32.3% female gender, dilated cardiomyopathy in 77.4%). Among these patients, 24 were randomized to MPP ON, 28 to MPP OFF. Six patients died and 4 were lost to follow-up. Baseline clinical and echocardiographic characteristics were similar between groups (p = NS). At 6 months, the overall response rate (reduction in ESV≥15%) was 75%. At twelve months, patients randomized to MPP ON had a super-response rate (reduction in ESV≥30%) higher than patients with MPP OFF (75% vs 39.3%, p = 0.01). Between 6-12 months, patients assigned to MPP ON had a higher reduction in ESV (93.4 ± 52.3mL to 82.1 ± 40.5mL, p = 0.04) and an improvement in LVEF (38.3 ± 9.8% to 45.1 ± 11.1%, p < 0.01) compared to patients with MPP OFF (92.2 ± 47.3mL to 95.4 ± 47.5mL, p = NS; 37.1 ± 12.0% to 40.2 ± 9.2%, p = NS). Additionally, QoL of patients with MPP ON improved during follow up (EQ-5D 78.3% to 86.3%, p < 0.01; MLWHF 12.1 to 6.6, p = 0.03, 6MWT 316m to 239m, p = NS; NTproBNP 1608 ± 2450pg/mL to 775 ± 914pg/mL, p = NS) and was unchanged in MPP OFF patients (76.6% to 74.2%; MLWHF 12.7 to 12.7; 6MWT 338m to 299m, NTproBNP 1112 ± 1442pg/mL to 1383 ± 2118pg/mL, for all p = NS). Conclusion: In our population, patients with CRT programmed with MPP ON, when compared to MPP OFF, had an improvement in the super-response rate and in quality of life. These results may be consequence from a more favorable reverse remodeling due to MPP, with a higher reduction in the LV end systolic volume.